Is a higher frequency of esophageal dilations more effective in treating benign esophageal strictures? Retrospective, multicenter study - Graf, Christiana; Reden, Monika; Blasberg, Tobias; Knabe, Mate; May, Andrea; Ell, Christian; Wedi, Edris; Wetzstein, Nils; Michael, Florian; Zeuzem, Stefan; Bojunga, Jörg; Friedrich-Rust, Mireen (Endoscopy International Open, 2024)
Background and study aims There is still a lack of evidence-based recommendations concerning endoscopic bougienage in benign esophageal strictures. Our study aimed to assess the relevance of the time interval between endoscopic dilation (ED) sessions with regard to endoscopic and clinical response.Patients and methods We performed a retrospective study including patients treated with endoscopic bougienage for a benign esophageal stricture in two German centers. Primary endpoint was the number of ED until freedom from dysphagia was achieved. Secondary endpoints were analyses on reaching a diameter of 15 mm and on achieving clinical freedom from symptoms.Results Between April 2014 and March 2020, bougienage was used as the primary treatment for benign esophageal strictures in 238 patients (194 patients in Center 1; 44 patients in Center 2). Both centers differed in their endoscopic bougienage regime: Center 1 was characterized by a higher frequency of interventions compared to Center 2 (median: 2 days [range 1–28] vs. 10 days [range 1–41]; P<0.001). Clinical response was achieved significantly earlier using the high-frequency regimen in all patients except for those with post-radiogen strictures, who clinically benefited from a low-frequency ED program. Accordingly, patients receiving higher-frequency ED reached a significantly larger post-dilation diameter and considerably larger diameter differences.Conclusions The results of our study demonstrate that a treatment concept consisting of higher-frequency bougienages seems to be more effective in treating most types of esophageal stricture. Radiogenic strictures were the only types of stenoses that benefited from a lower frequency ED program.
Keywords: Reflux disease; Benign strictures; Endoscopy Upper GI Tract; Dilation, injection, stenting; Malignant strictures